Analysis of Carpet Orders to Suppliers at PT Distributor Karpet Bandung (dkb) Using Probabilistic Economic Order Quantity - Waskito, Saptono Kusdanu; Rahayu, Muji (Dinasti International Journal of Digital Business Management, 2023)
PT Distributor Karpet Bandung (DKB) is a distribution services company that sells Eva Carpets in the city of Bandung. DKB purchased Eva Carpets from Suppliers in Jakarta. The number of Eva Carpet purchases in 2023 will be as much as Eva Carpet sales in 2023 will be 106,614 units, 107,000 units. The initial inventory in 2023 will be 500 units. There is excess inventory of 886 units. The author conducted research with the title "Analysis of Carpet Orders to Suppliers at PT Distributor Kartpet Bandung (DKB) Using the Probabilistic EOQ Method". The author analyzed Eva Carpet purchase orders using the Probabilistic EOQ Method by forecasting sales numbers from January 2024 to December 2024 using the linear regression method. The research results explain that the number of Eva Carpet sales calculated using the linear regression method for 2024 is 106,617 units. 3 more units than actual sales in 2023. The calculation result of the number of units purchased for each order using the Economic Order Quantity method is 38,727 units. Inventory costs before using EOQ are IDR 177,263,700. Costs after using EOQ are IDR 63,032,850. Inventory Cost Savings amounting to IDR 114,230,858. It is best for DKB to plan Eva Carpet purchase orders using the Probabilistic EOQ method.